2016
DOI: 10.4037/ccn2016362
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Deactivation of Implantable Cardioverter Defibrillators at the End of Life in Patients With Heart Failure

Abstract: Implantable cardioverter defibrillators (ICDs) may be burdensome in end-stage heart failure. At the end of life, as many as one-fifth to one-third of patients experience an ICD shock. Critical care nurses should be aware of the potential burden of these shocks at the end of life as well as the ethics and organizational policies surrounding ICD deactivation. This literature review examines the issues surrounding ICD therapy at the end of life. Based on this author's findings, recommendations for discussing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
1
10
0
3
Order By: Relevance
“…Health care professionals working in HF care should openly discuss any issue related to the illness trajectory, including prognosis, symptom management, options and preferences for palliation and end-of-life care as well as deactivation of devices with patients and their families. By doing so, the professionals help them to be prepared to live with a life-limiting illness and for the last phase of life [ 4 , 5 ]. However, this open approach to communication about the HF trajectory is not widely implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Health care professionals working in HF care should openly discuss any issue related to the illness trajectory, including prognosis, symptom management, options and preferences for palliation and end-of-life care as well as deactivation of devices with patients and their families. By doing so, the professionals help them to be prepared to live with a life-limiting illness and for the last phase of life [ 4 , 5 ]. However, this open approach to communication about the HF trajectory is not widely implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…14 Odnětí život prodlužující přístrojové léčby na konci života je často kontroverzní, a ačkoliv deaktivace ICD je všeobecně akceptovaná, ne každý pacient či zdravotnický pracovník s ní souhlasí. 15 Důvody nesouhlasu mohou být různé. Jednou z častých obav je strach z eutanazie, tedy že deaktivace ICD nebo i jiné podobné jednání by mohlo vzbudit podezření z ní.…”
Section: úVod Do Problematiky a Etické Principyunclassified
“…Každopádně je důležité otevřít toto téma včas, kromě doby implantace také v období závažnějších změn zdravotního stavu, avšak ještě před jeho terminální deteriorací. 1,15 Obecným cílem komunikace lékaře s pacientem je v tomto případě diskuse, v rámci níž pacient pochopí podstatu svého onemocnění a cíle léčby, které se mohou dynamicky měnit s trajektorií nemoci nebo příchodem závažných přidružených onemocnění. Relativní obtížnost či nepříjemnost tématu pro lékaře nemůže být důvodem pro nekomunikaci.…”
Section: Komunikace S Pacientemunclassified
See 1 more Smart Citation
“…Discussing end-of-life care also includes discussions about withholding cardiopulmonary resuscitation and deactivating ICDs for patients who have these devices (52,69,70). It has been shown that many patients have several ICD shocks during the last days of their life, and that discussions about deactivation rarely take place (43,44).…”
Section: End-of-life Carementioning
confidence: 99%